1993
DOI: 10.1177/0032855593073001005
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Determinants of the Prison Experience

Abstract: This article applies the tec.~nology of psychological classification to explore the effects of personality characteristics on prison adjustments and experiences. Bivariate and multivariate analysis assess the comparative effects offour personality types (committed criminal, neurotic, situational, and character disordered) on official disciplinary infractions, staff ratings of interpersonal behaviors, and self-reports of • stress, aggressive behaviors, nonviolent infractions, and victimizations. The effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 28 publications
0
21
1
Order By: Relevance
“…Consistent with the importation model of inmate behavior, prior research has shown that criminal history is strongly related to institutional misconduct (Berg & DeLisi, 2006;Byrne & Hummer, 2007Cunningham & Sorensen, 2007;DeLisi, 2003;DeLisi & Muñoz, 2003;Gendreau, Goggin, & Law, 1997;Myers & Levy, 1978;Trulson, 2007;Van Voorhis, 1993). DEPENDENT VARIABLES Four types of misconduct were included that span multiple dimensions of externalizing behaviors as is conventional in penological research (DeLisi et al, , 2009Steiner & Wooldredge, 2008, p. 452;Trulson et al, 2010;cf.…”
Section: Delinquency Historymentioning
confidence: 98%
“…Consistent with the importation model of inmate behavior, prior research has shown that criminal history is strongly related to institutional misconduct (Berg & DeLisi, 2006;Byrne & Hummer, 2007Cunningham & Sorensen, 2007;DeLisi, 2003;DeLisi & Muñoz, 2003;Gendreau, Goggin, & Law, 1997;Myers & Levy, 1978;Trulson, 2007;Van Voorhis, 1993). DEPENDENT VARIABLES Four types of misconduct were included that span multiple dimensions of externalizing behaviors as is conventional in penological research (DeLisi et al, , 2009Steiner & Wooldredge, 2008, p. 452;Trulson et al, 2010;cf.…”
Section: Delinquency Historymentioning
confidence: 98%
“…Most recent research on inmate social life, adjustment, and prisonization has focused almost exclusively on general prison populations without consideration for inmate social and economic status (see, Adams, 1992;Gendreau, Goggin, & Law, 1997;MacKenzie, Robinson, & Campbell, 1989;Toch & Adams, 1989;Van Tongeren & Klebe 2010;Van Voorhis, 1993, 1994Walters, 2005;Wooldredge, 1999;Wright, 1988Wright, , 1991Wright, , 1993Wright, Salisbury, & Van Voorhis, 2007;Zamble, 1992;Zamble & Porporino, 1988). As a result, we have had no way of knowing how white-collar inmates in federal prison adjust to their incarceration, despite the suggestion by criminologists, judges, and the public that prisons can be dangerous and depriving environments for this subset of offenders.…”
Section: Rising Rates Of White-collar Incarcerationmentioning
confidence: 99%
“…Theoretically, variables that are risk factors for offending in society at large should correspond to risk factors for prison misconduct. To date, criminologists have found that defendants with more extensive arrest and incarceration histories, prior involvement with gangs or security threat groups, serious substance abuse problems, or previous use of violence were among the most difficult-to-manage inmates (Cao, Zhao, & Van Dine, 1997;DeLisi, 2003;DeLisi, Hochstetler, & Murphy, 2003;Flanagan, 1983;Gaes, Wallace, Gilman, Klein-Saffran, & Suppa, 2002;Gendreau, Goggin, & Law, 1997;Harer & Langan, 2001;McCorkle, 1995;Schrag, 1954;Thomas & Cage, 1977;Van Voorhis, 1993).…”
Section: Deprivation Importation and Their Integrationmentioning
confidence: 99%